POTAMOGETONACEAE EN LA FLORA VASCULAR ACUATICA DEL PARQUE NACIONAL NATURAL CHINGAZA, COLOMBIA (2013)
Sampling of the aquatic vascular flora of the Chingaza National Natural Park (Colombia) allowed the initial taxonomic description of the Potamogetonaceae, Potamogeton paramoanus Haynes & Holm-Nielsen and P. illinoensis Morong found in the area of study. Descriptions of the family, genus, keys, illustrations and general notes on their distribution and ecology are given.